Impact of COVID-19 on neuropsychiatric disorders and mental health - David, Anthony (Henry Stewart Talks, 2021)
Possible causal links between COVID-19and the emergence of neuropsychiatric disorders, Change in prevalence of neuropsychiatric disorders over the past (COVID-19) year, Impact of the disease itself on mental health, Impact of social distancing and isolation on mental health, Longer-term impact of COVID-19 on the evolution of neuropsychiatric disorders and mental health in general